(untitled) (Journal of Science and Technology, 2025)
Understanding research philosophies and approaches are important for identifying appropriate research design, their suitability, reliability and validity for research projects. Here, research philosophies and approaches employed by contributors to the Journal of Science and Technology (JUST) from the year 2000 to 2020 are reviewed. All papers (580 articles) were retrieved from African Journals Online (AJOL), the KNUST institutional repository and the JUST Website. The papers were grouped to reflect the academic disciplines offered at KNUST, the publishers of JUST. The abstracts of the papers were first scrutinised to appreciate the contents and collated keywords. Thereafter, the introduction, materials and methods, results, discussion, and conclusions sections were thoroughly critiqued. The findings revealed that positivism rooted in deductive reasoning dominates the JUST accounting for 87.8% of articles. The use of quantitative analytical tools namely, statistical analysis (68.27%), simulation (7.41%) and mathematical modelling (0.17%) featured in the order presented. Interpretivism rooted in inductive reasoning/qualitative analytical tools represented 14.31% in use. Agriculture, Health and Pure Sciences widely used statistics whilst disciplines in Engineering relied mostly on simulation and modelling. While Agriculture used mostly inferential statistics, the health-related disciplines produced mostly descriptive statistics. Social sciences and humanities including Library and Information studies relied largely on descriptive statistics except economics, which was dominated by inferential statistics. Built environment research relied largely on descriptive statistics while Art-based programmes rely largely on qualitative approaches and narrations. These findings are important in helping the JUST to identify the strengths and weak areas towards encouraging a multi philosophically inclusive publications in the JUST, as a multidisciplinary academic journal. The findings could be helpful to the management of JUST and interested stakeholders towards expanding the profile of research publications knowledge promotion and as training manual for potential authors.